The delusion of the specialist. Notes on The Gutenberg Galaxy by Marshall McLuhan - Serra, Marcello (Anuario ThinkEPI, 2023)
With the publication of The Gutenberg Galaxy, Marshall McLuhan proposed a science of media situated at the core of the sciences of culture. More than six decades later, communication studies seem to have abandoned such ambitions. This text reconstructs the main ideas of the book and reflects on its contemporary relevance. It specifically focuses on the function of McLuhan’s “mosaic” writing and the questions that his method continues to raise for the field of communication studies.
Keywords: McLuhan; Medium theory; Specialism; Research in communication